A review on current knowledge of major zoonotic protozoan diseases affecting farm and pet animals - Ragab Fereig; Hanan Abdelbaky; Kousuke Umeda; Thu-Thuy Nguyen; Adela Mohamed (German Journal of Veterinary Research)
Given the high importance of animal uses for human being, avoidance of contact with animals is far from straightforward even if there is a risk of zoonotic diseases. Animal products or byproducts are essential source of food for human. Also, there are large numbers of companion animals worldwide which are important for the soundness of mental health for the owners. Understanding of the disease in animals is of paramount importance to control and prevent transmission to human. Zoonotic protozoan parasites, including malaria, babesiosis, trypanosomiasis, toxoplasmosis and cryptosporidiosis, can cause severe infections to human and some of them can drastically affect both economy and society. Impacts of such infections are aggravated when asymptomatic animals being in contact with susceptible individuals including infants, pregnant women or immunocompromised people. Malaria, babesiosis and trypanosomiasis are vector-borne diseases that cause hemolytic anemia and high fever. Toxoplasmosis is a congenitally transmitted infection characterized by abortion and congenital abnormalities in infected persons and animals. Cryptosporidiosis is a highly contagious disease affecting human and various animal species and diarrhea is the main clinical form. These infections are globally distributed and affect various demographics. However, awareness of these often neglected diseases in almost all countries and communities are required for protecting animals, owners and customers. Thus, this review is aimed to provide the recent and current knowledge on transmission, epidemiology and control of some protozoan diseases of zoonotic importance.